إدارة المخاطر في المصارف التجارية - صقر, محمد علي; أحمد, هادي محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
على الرغم من وجود أكثر من مفهوم للمخاطر التي يمكن أن تتعرض لها المصارف التجارية من خلال التطورات الحاصلة في آليات عمل المصارف التجارية وتنوع الخدمات المصرفية المقدمة للزبائن, إلا أن هذه المفاهيم كافه أجمعت على أنها ذات تأثيرات سلبية على درجة أعمال المصرف و تحقيق الأهداف المنشودة للمصارف التجارية. من هنا كان لا بد لإدارة المصرف التجاري التعامل مع هذه المخاطر من خلال أسلوب إدارة المخاطر بهدف التعرف على المخاطر ومعرفة أنواع المخاطر التي تتعرض لها المصارف و قياسها من خلال احتمالية حدوث الخطر وتوقيت الخطر وتقييمها وترتيبها وفق الأولويات من الأكثر خطورة إلى الأقل خطورة وذلك باستخدام أسلوب المصفوفات المرجحة لتسليط الضوء على المخاطر العالية و توجيه الاهتمام نحو معالجتها . Although there is more than a concept of risk that can be experienced by commercial banks through developments in the mechanisms of commercial banks and diversity of banking services provided to clients, all of these concepts were unanimous as having a negative impact on the degree of the bank's business and achieve the desired goals to commercial banks. So it was necessary to manage the commercial bank to deal with these risks through a method of risk management in order to identify the risks and see what kinds of risks faced by banks and measured by the probability of the risk and timing risk and evaluated and ranked according to the priorities of the most serious to less serious using a weighted matrix method to highlight the high-risk and direct attention to address the same.